Prognosis tools for short-term adverse events in older emergency department users : result of a Québec observational prospective cohort - Launay, Cyrille P. (2021)
Background: The “Program of Research on the Integration of Services for the Maintenance of Autonomy” (PRISMA-7) and “Emergency room evaluation and recommendations” (ER2) are both clinical tools used in Québec Emergency Departments (EDs) for screening of older ED users at higher risk of poor outcomes, such as prolonged length of stay (LOS) in EDs and in hospital. The study aimed to: 1) examine whether the PRISMA-7 and ER2 risk levels were associated with length of stays in ED and hospital, as well as hospital admission; and 2) compare the criteria performance (i.e., sensitivity, specificity, positive predictive value, negative predictive value, likelihood ratios and area under receiver operating characteristic curve) of the PRISMA-7 and ER2 high-risk levels for these three ED adverse events in Québec older patients visiting ED on a stretcher. Methods: A total of 1905 older patients who visited the ED of the Jewish General Hospital (Montreal, Québec, Canada) on stretchers were recruited in this prospective observational cohort. Upon their ED arrival, PRISMA-7 and ER2 were performed. The outcomes were LOS in ED and in hospital, and hospital admission. Results: The PRISMA-7 and ER2 risk levels were associated with length of stay in ED and hospital as well as with hospital admission. Prolonged stays and higher hospitalization rates were associated with high-risk levels, whereas those in low-risk level groups had significantly shorter LOS and a lower rate of hospital admission (P < 0.006). While performance measures were poor for both assessment tools, ER2 had a greater prognostic testing accuracy compared with PRISMA-7. Conclusion: PRISMA-7 and ER2 were both associated with incidental short-term ED adverse events but their overall prognostic testing accuracy was low, suggesting that they cannot be used as prognostic tools for this purpose.